Proceedings of the 18th ACM International Conference on Interaction Design and Children 2019
DOI: 10.1145/3311927.3325312
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Social and Temporal Aspects of Children's Physical Activity Games

Abstract: There are a variety of fitness technologies such as activity trackers, exergames and mobile applications available to promote physical activity. Based on our previous research, we found that children prefer having social interaction, a narrative and flexibility while interacting with such technologies. Other research has shown that persuasive displays encouraged adults towards physical activity. In this research, we present the initial results from a user study conducted on 16 children (ages 6-11) who used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…the physical and societal aspects, is vital, especially to ensure relevance of place-making for children [6]. In this process, children need to have flexibility [42] to define their own rules [22], and social interaction and collaboration are key [32,42].…”
Section: Place-making Processes For Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…the physical and societal aspects, is vital, especially to ensure relevance of place-making for children [6]. In this process, children need to have flexibility [42] to define their own rules [22], and social interaction and collaboration are key [32,42].…”
Section: Place-making Processes For Childrenmentioning
confidence: 99%
“…A method to invite children to consider outdoor play activities that can be played using the physical elements of their neighbourhood, potentially complemented with a digital mobile app, would seem in line with these findings. Further, as social interaction and collaboration are identified as key elements to successful placemaking [32,42], they should be central in both the PD method and activities. Finally, the need for flexibility for children to create their own rules of game for meaningful interaction is well-recognised [22,42].…”
Section: Place-making Processes For Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…narratives, social interactions, and activities to create fun experiences required for young children [22]. Having studied interaction patterns among children and technology, the authors of Reference [8] observed that children want stories, a relationship with characters, to collect, to be creators and to be in control.…”
Section: Research On Technologies Addressing Social-emotional Learningmentioning
confidence: 99%